Browning's experiments with genre - Hair, Donald S. ([Buffalo, New York] : University of Toronto Press, 1972)
This book explores the kinds and modes with which Browning worked and describes the nature of the experiments he made, concentrating on the earlier poetry and in particular on The Ring and the Book.
"1 The Early Poems" -- "Pauline" -- "Paracelsus" -- "Sordello" -- "2 The Plays" -- "Strafford" -- "Pippa Passes" -- "A Blot in the 'Scutcheon" -- "Luria" -- "3 Poems 1842-64" -- "Romance" -- "Lyric" -- "Men and Women" -- "4 The Ring and the Book" -- "Lyric" -- "Narrative" -- "Drama" -- "The Patterns of the Poem" -- "Half-Rome" -- "The Other Half-Rome" -- "Tertium Quid" -- "Count Guido Franceschini" -- "Giuseppe Caponsacchi" -- "Pompilia" -- "Dominus Hyacinthus de Archangelis" -- "Juris Doctor Johnannes-Baptista Bottinius" -- "The Pope" -- "Guido" -- "The Book and the Ring" -- "Conclusion."
Based on the author's thesis, University of Toronto.
Includes bibliographical references (pages 185-191) and index.
JSTOR
Keywords: Browning, Robert, -- 1812-1889 -- Technique; Browning, Robert -- Critique et interprétation.; Browning, Robert, -- 1812-1889; Literature, Experimental -- History and criticism; Literary form -- History -- 19th century; Poetics -- History -- 19th century; Littérature expérimentale -- Histoire et critique; Genres littéraires -- Histoire -- 19e siècle.; Poétique -- Histoire -- 19e siècle.; Literary form; Literature, Experimental; Poetics; Technique; 1800-1899; Criticism, interpretation, etc; History